Anytime motion planning for prehensile manipulation in dense clutter. (17th November 2019) - Kimmel, Andrew; Shome, Rahul; Bekris, Kostas
ABSTRACT: Many methods have been developed for planning the motion of robotic arms for picking and placing, ranging from local optimization to global search techniques, which are effective for sparsely placed objects. Dense clutter, however, still adversely affects the success rate, computation times, and quality of solutions in many real-world setups. The proposed method achieves high success ratio in clutter with anytime performance by returning solutions quickly and improving their quality over time. The method first explores the lower dimensional end effector's task space efficiently by ignoring the arm, and build a discrete approximation of a navigation function. This is performed online, without prior knowledge of the scene. Then, an informed sampling-based planner for the entire arm uses Jacobian-based steering to reach promising end effector poses given the task space guidance. This process is also comprehensive and allows the exploration of alternative paths over time if the task space guidance is misleading. This paper evaluates the proposed method against alternatives in picking or placing tasks among varying amounts of clutter for a variety of robotic manipulators with different end-effectors. The results suggest that the method reliably provides higher quality solution paths quicker, with a higher success rate relative to alternatives. GRAPHICAL ABSTRACT: